PERAN TEKNOLOGI DI DUNIA ISLAM - Aan Rukmana (Institut PTIQ Jakarta, 2019)
Islam since the beginning of its birth has encouraged science. The command “iqra” is authentic evidence of how Islam loves science. This evidence shows that Islam has a major contribution to the deve-lopment of science, including technology in it. This paper attempts to explain the contribution of Islam to technological development from the classical Islamic period to the current era. ICT is a contemporary problem facing Muslims. There are two choices, whether to reject ICT or accept it. This paper focuses on how Muslims can accept ICT for de-veloping the Islamic scholarship